Antibiótico Profilaxis de Amoxicilina en Ruptura Prematura de membranas de 28 a menos de 37 semanas, en el hospital “Víctor Lazarte Echegaray” entre Enero y Diciembre de 1996 - Ríos Canales, Cecilio Isaac (1998)
Forty pregnant women 0f 28 until 37 weeks, with premature rupture of membranes (R.P.M.) that were given prophylactic treatment with Amoxiciline at the Obstetrics Service of the “Víctor Lazarte Echegaray” Hospital IPSS – Trujillo from January to December 1996. It was found an incidence of 2.28%. The average age of the patients was 33.25% years old, with S.D +-5.2, with a range of 22 a 44 years old. The average gestacional age was 34.77 weeks, with S.D. +-2.5; with a mediun duration of R.P.M. of 27.9 hours, with S.D. +-21. The majority had eutocic labour (67.5%). with Newborn of masculine sex and feminine sex in equal propotion (50%), with average weight of 2,500 g., with S.D. +-566.5. with Apgar of 7-10(87.5%) at one minute, and the five minute (97.5%) and the asphyxia grade decreased to 2.5%. The prophylactic treatment with Amoxiciline with the dose of 500 mgs. each 8hours orally; protected the mother in 92.5%, being highly significant between the 6 and 24 hours of prophylactic treatment beginning (p<0.001). There was protection of infection of the Newborn between the 6 hours (90%) and 24 hours. (67.5%). Being highly significant (p<0.001). From the 72 hours we found maternal infections: Corioamnionitis (5.0%), and Endometritis (2.5%), and in the Newborn: Pneumonia (5.0%), Conjutivitis and Sepsis in 2.5%, respectively. There was mortality of a Newborn (2.5%) of masculine sex, of 28 gestacional weeks, of 1,700 grams, with R.P.M. of 19 days, wich cause was Hyaline membrane (SDR) and sepsis.